Community Empowerment-Based Educational Management to Support Sustainable Development through Water Hyacinth Utilization for Biogas Production - Novianti Muspiroh (Lembaga Bale Literasi, 2025)
The rapid proliferation of water hyacinth caused by eutrophication is widely recognized as an environmental burden; however, existing studies have predominantly emphasized technological optimization for biogas production while overlooking the critical role of educational management in transforming ecological problems into sustainable community assets. This gap has limited a comprehensive understanding of how education, community empowerment, and renewable energy can be integrated to achieve sustainable development. This study aims to develop a community empowerment-based educational management model that transforms water hyacinth into biogas as a strategy for promoting sustainable development in Sukapura, Cirebon City, Indonesia. A qualitative intrinsic case study was employed using observations, in-depth interviews, focus group discussions, documentation, and secondary data. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña, supported by triangulation, prolonged engagement, audit trails, and peer debriefing to ensure trustworthiness. The findings reveal that the success of water hyacinth utilization is determined not primarily by biomass availability or technological sophistication, but by educational management that strengthens environmental literacy, experiential learning, community participation, collaborative governance, and local institutional capacity. Educational intervention transformed community perceptions of water hyacinth from an invasive aquatic weed into a strategic renewable energy resource while simultaneously fostering social cohesion, local energy resilience, and circular economy practices. The study proposes a novel conceptual model integrating Education for Sustainable Development, community empowerment, experiential learning, appropriate technology, and circular bioeconomy within a unified educational management framework. These findings extend the current discourse by positioning educational management as the principal catalyst for community-based renewable energy transitions. Future research should validate this model across diverse socio-ecological contexts using mixed-methods or longitudinal designs and incorporate carbon emission assessment, life cycle analysis, and digital technologies to support evidence-based renewable energy policies and sustainable community development.